(untitled) (Marketing Journal, 2025)
This article examines the impact of improving the local governance system on the export potential of regions. Using the cases of Fergana, Khorezm, and Surkhandarya provinces, the study analyzes reforms implemented between 2019 and 2024. Statistical and eco nometric methods are applied to assess the effects of establishing export coordination units, introducing digital services, and developing trade -logistics centers at the regional level. The findings indicate that local governance reforms have significantly contributed to increasing export volumes and diversifying products. The paper also highlights the importance of enhancing human capital, infrastructure, and innovation adoption for sustainable export growth in the future. 203